Simulation and Experimental Study of Photogeneration and Recombination in Amorphous-Like Silicon Thin Films Deposited by 27.12 MHz Plasma-Enhanced Chemical Vapor Deposition - Chia-Hsun Hsu; In-Cha Hsieh; Chia-Chi Tsou; Shui-Yang Lien (International Journal of Photoenergy)
Amorphous-like silicon (a-Si:H-like) thin films are prepared by 27.12 MHz plasma-enhanced chemical vapor deposition technique. The films are applied to p-i-n single junction thin film solar cells with varying i-layer thickness to observe the effects on the short-circuit current density, as well as the open-circuit voltage, fill factor, and conversion efficiency. The most significant experimental result is that Jsc has two different behaviors with increasing the i-layer thickness, which can be related to carrier collection efficiency in the long wavelength region. Furthermore, technology computer-aided design simulation software is used to gain better insight into carrier generation and recombination of the solar cells, showing that for the i-layer thickness of 200 to 300 nm the generation dominates the carrier density and thus Jsc, whereas for the i-layer thickness of 300 to 400 nm the recombination becomes the leading factor. The simulation results of cell performances are in good agreement with experimental data, indicating that our simulation has great reliability. In addition, the a-Si:H-like solar cells have low light-induced degradation, which in turn can have a great potential to be used for stable and high-efficiency solar cells.